Expanded newborn screening in the Health Services of the Mexican Navy - Max Trigo-Madrid; Javier Díaz-Gallardo; Roberto Mar-Aldana (Instituto Nacional de Pediatría, 2014)
In Mexico the birth prevalence of the metabolic diseases detected by expanded newborn screening is poorly known and there is little information about its performance indicators.Objective. Describe the birth prevalence of the metabolic defects detected by the expanded newborn screening program implemented in the Mexican Navy (Secretaría de Marina Armada de México, SEMAR), and to make known some of its performance indicators. Materials and Methods. A blood sample of 5 205 newborns from 18 Mexican states were taken. The age at blood sampling, the proportion of samples taken between the 3rd and the 5th days of life, and the time of results delivery were analyzed. The number and type of detected metabolic diseases, as well as the maternal age and body mass index, the type of birth, the gestational age and weight of the newborns were analized. Results. The age at blood sampling was 4.7 days and 81.15 percent of the samples were obtained in optimal time. Two cases of congenital hypothyroidism (3.8/10 000 newborns), one of adrenal congenital hyperplasia (1.9/10 000 newborns) and five cases of deficiency of glucose- 6-phosphate dehydrogenase (9.6/10 000 newborns) were detected. The 85.6% of mothers had pregnancies at an optimal reproductive age (20-35 years), but overweight and obesity occurred in 44.7% of them. Conclusions. In this analyzed population, the birth prevalence of metabolic defects was 15.37/10 000 newborns. The expanded newborn screening program allowed its identification and timely treatment, with the aim of preventing disability and death.